Features of lung morphology in the grass frog (Rana temporaria) - Horalskyi, L. P.; Tsanko, I. V.; Romaniuk, R. K.; Gutyj, B. V.; Tsekhmistrenko, S. I.; Dmytruk, V. S. (Regulatory Mechanisms in Biosystems, 2026)
One of the essential functions of the organism is to provide cells and tissues with oxygen and nutrients and to remove metabolic products, which is ensured by the respiratory organs. T he present study reports the results concerning the morphotopography and morphological structure of the lungs of the grass frog ( Rana temporaria familiaris L innaeus , 1758). The lungs of the frog are located in the cranial part of the body cavity, medially adjacent to the esophagus and ve n trally bordering the right and left atria of the heart. Laterally, the right lung is adjacent to the right lobe of the liver, whereas the left lung borders the cardiac part of the stomach. The lungs are paired organs of dark pink color formed by the right and left lungs, representing elongated, oval-shaped sac-like structures. Their absolute mass is 0.12 g, and the relative mass is 0.18%. According to the lung development index, which averages 42% (right lung – 43.1%, left lung – 41.8%), the lungs of the grass frog belong to the expanded - shortened type. The lung walls are formed by three layers: the outer layer, consis t ing of a thin layer of simple squamous epithelium and a layer of loose connective tissue; the middle layer, formed by dense regular connective tissue containing reticular and collagen fibers; the inner layer, lined with simple single-layered epithel i um under which there is a layer of loose connective tissue. The walls of the right and left lungs form folds and villous projections that branch into the depth of the organ cavity, thereby increasing the respiratory surface of the lungs. The vo l ume of the right lung is 216 mm³, while the volume of its cavity is 157 mm³; the ratio of the cavity volume to the total lung volume is 0.73%. In the left lung, the morphometric parameters are similar: the lung volume is 199 mm³, the cavity vo l ume is 147 mm³, and the ratio of the cavity volume to the total lung volume is 0.41%, which indicates the absence of pr o nounced asymmetry between the left and right lungs.